Efektivitas Model Pembelajaran Kooperatif Berbantuan Metode Kumon Terhadap Hasil Belajar Matematika Siswa Kelas V UPTD SDN 198 Inpres Suli Suli Kec. Bontoa Kab. Maros - Jusmawati Jusmawati; Andi Husniati; Kristiawati Kristiawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The background of this research is that students do not participate in the learning process because educators still use conventional learning models so that the learning process looks boring. This type of research is pre-experimental research. The research design used was One Group Pretest-Posttest. The experimental sample in this research was class V students of UPTD SDN 198 Inpres Suli Suli Kec. Bontoa Kab. Maros as many as 22 people. The research was carried out over 6 meetings.The data collection techniques used were learning outcomes tests and student response questionnaires. The results showed that: (1) the average pretest score of students before the Kumon method-assisted cooperative learning model was applied was 55,45 while the posttest average score after the Kumon method-assisted cooperative learning model was applied was 87,27. From these results, it was obtained that 0 (0%) students did not complete and 22 (100%) students completed, this means that classical completion was achieved. (2) There was an increase in student learning outcomes after implementing the cooperative learning model assisted by the Kumon method where the average normalized gain value was 0,69 and was generally in the high category. (3) The average percentage of student activity for each indicator reaches the effective criteria, namely 80%. (4) The student response questionnaire showed that the student response to the cooperative learning model assisted by the Kumon method was positive, namely 43,6%. (5) The results of the analysis of learning implementation with an average value of 3,88.